Flame-retardant insulated polyvinyl chloride cable and preparation process thereof
Through the combined technology of polybenzimidazole coated mica particles and repair microcapsules, the problem of insufficient flame retardancy and insulation performance of traditional polyvinyl chloride cables is solved, and higher flame retardant and insulation performance is achieved, reducing fire risk and safety hazards.
Patent Information
- Application Number
- CN202411270652.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The flame retardant and insulation properties of traditional polyvinyl chloride cables are insufficient, the flame retardant is poorly dispersed, fails at high temperatures, and is prone to deformation and damage under the influence of external forces and environment, and there are fire and safety hazards.
Polybenzimidazole coats mica particles and repair microcapsules, and is impregnated by phosphate solution and protected by epoxy resin shell to improve component compatibility and flame retardant performance, and enhance the flame retardant and insulation performance of the cable.
It significantly improves the flame retardancy and insulation of the cable, enhances the ability to withstand high temperatures and external forces, extends the insulation effect, and reduces fire risks and safety hazards.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of cables and relates to a flame-retardant insulated polyvinyl chloride cable and a preparation process thereof. Background Art
[0002] With the rapid development of modern society, the importance of electricity and communications in various fields has become increasingly prominent. As an important carrier for power transmission and signal transmission, polyvinyl chloride cables are widely used in many fields such as construction, industry, communications, and transportation. With the diversification of application scenarios, the demand for high-performance cables continues to grow.
[0003] The flame retardancy and insulation performance of traditional PVC cables need to be improved. For example, the flame retardant of traditional PVC cables has poor dispersion and is difficult to be evenly distributed throughout the cable material, resulting in unsatisfactory flame retardant effects in some areas. In addition, the existing flame retardant system is not stable enough at high temperatures. As the temperature rises, the flame retardant may decompose or lose its activity and cannot continue to play a flame retardant role. In the event of a fire, the cable may burn and spread rapidly, increasing the risk of fire. In addition, when PVC cables are pulled, squeezed or bent by external forces, they are prone to deformation and breakage. With the increase of use time and the influence of environmental factors, the insulation performance of PVC cables will gradually decrease. When the insulating material is subjected to high voltage, local discharge is prone to occur, posing a major safety hazard. Summary of the invention
[0004] The object of the present invention is to provide a flame-retardant insulated polyvinyl chloride cable and a preparation process thereof. In the preparation process of polybenzimidazole-coated mica particles, the present invention performs two phosphate solution impregnation treatments to improve the compatibility and flame retardancy between components, and simultaneously prepares repair microcapsules, protects the repair agent with an epoxy resin shell, releases polyurethane prepolymers under external force or high temperature, thereby filling cracks, and effectively improving the overall flame retardancy and insulation of the cable.
[0005] The purpose of the present invention can be achieved by the following technical solutions:
[0006] A preparation process of a flame-retardant insulated polyvinyl chloride cable, the preparation process comprising the following steps:
[0007] (1) adding polyvinyl chloride resin, polybenzimidazole-coated mica particles, and repair microcapsules into a high-speed mixer and mixing and stirring to obtain material 1;
[0008] (2) adding a plasticizer, a stabilizer and a lubricant to the material 1, stirring and then ultrasonically treating, to obtain a material 2;
[0009] (3) placing the second material in a twin-screw extruder for melt extrusion and then placing it on a roller for refining to obtain a flame-retardant insulating polyvinyl chloride material;
[0010] (4) Extruding the flame-retardant insulating material on the outer surface of the wire core and cooling it to obtain a flame-retardant insulated polyvinyl chloride cable.
[0011] Furthermore, in step (1), the mass ratio of the polyvinyl chloride resin, the polybenzimidazole-coated mica particles and the repair microcapsules is 5.7-7.1:2.1-2.6:0.9-1.3; the molecular weight of the polyvinyl chloride resin is 180,000-220,000; and the parameters of the high-speed mixer are: stirring temperature is 100-140°C, stirring speed is 1200-1800rmp, and stirring time is 20-40min.
[0012] Furthermore, the preparation method of the polybenzimidazole-coated mica particles is:
[0013] V1. Mix 0.8-1.5 parts by weight of polybenzimidazole and 4-10 parts by weight of N,N-dimethylacetamide, and stir at 60-80° C. and 100-500 rpm for 1.2-1.8 hours to obtain a polybenzimidazole solution;
[0014] V2. Immerse mica particles with an average particle size of 50-70 μm in a phosphate solution, perform ultrasonic treatment for 30-40 min, filter with a 500-mesh filter cloth, wash with anhydrous ethanol, and then dry in an oven at 80° C. for 3 h to obtain treated mica particles;
[0015] V3, 1.5-2.5 parts by weight of the treated mica particles, 6-8.2 parts by weight of a polybenzimidazole solution, 0.3-0.8 parts by weight of a nonylphenol polyoxyethylene ether solution and 0.1-0.5 parts by weight of γ-aminopropyltriethoxysilane are mixed, and stirred at 80-120° C. and 30-70 rpm for 2-3 hours to obtain a mixture;
[0016] V4. Immerse the mixture in a phosphate solution, perform ultrasonic treatment for 10-20 minutes, filter with a 500-mesh filter cloth, and wash with anhydrous ethanol to obtain polybenzimidazole-coated mica particles.
[0017] Furthermore, the phosphate ester solution is composed of phosphate ester and anhydrous ethanol in a mass ratio of 0.8-1.1:9-9.5; the nonylphenol polyoxyethylene ether solution in step V3 is composed of nonylphenol polyoxyethylene ether and anhydrous ethanol in a mass ratio of 2.3-3:0.4-0.8.
[0018] Furthermore, the parameters of the ultrasonic step are: ultrasonic frequency is 50-60kHz, and ultrasonic temperature is 40-50°C.
[0019] Furthermore, the preparation method of the repair microcapsule is:
[0020] W1. Add 1.8-3 parts by weight of epoxy resin to 6-8 parts by weight of acetone, then add 0.2-0.6 parts by weight of diethylenetriamine, and stir at 50-150 rpm for 1-2 hours to obtain a shell material solution;
[0021] W2, adding 0.8-2 parts by weight of polyurethane prepolymer to 6-12 parts by weight of deionized water, and then adding 0.016-0.04 parts by weight of sodium lauryl sulfate, and stirring at a speed of 800-2000 rpm to obtain a repair agent emulsion;
[0022] W3. Mix 1.2-1.9 parts by weight of the repair agent emulsion and 2.5-3.1 parts by weight of the shell material solution, stir at 45-65°C at a speed of 1000-1500 rpm for 2-3 hours, filter with a 200-mesh filter cloth after stirring, wash with deionized water, and dry in an oven at 70°C for 5 hours to obtain repair microcapsules.
[0023] Furthermore, in step (2), the mass ratio of material 1, plasticizer, stabilizer and lubricant is 5-6:0.7-1.1:0.05-0.12:0.01-0.05; the parameters of the ultrasonic treatment step are: ultrasonic frequency is 50-60kHz, ultrasonic temperature is 55-75°C, and ultrasonic time is 10-20min.
[0024] Furthermore, the temperature of the melt extrusion in step (3) is 195-215°C, and the temperature of the roller milling is 175-195°C.
[0025] Furthermore, the parameters of the extrusion step in step (4) are: extrusion temperature of 220-260°C, extrusion speed of 6-10m / min, and extrusion pressure of 7-9MPa; the parameters of the cooling step are: cooling temperature of 8°C and cooling time of 6min.
[0026] Beneficial effects of the present invention:
[0027] (1) The polybenzimidazole in the polybenzimidazole-coated mica particles of the present invention has high thermal stability and flame retardancy in molecular structure. The nitrogen atom in the imidazole ring can form hydrogen bonds with oxygen in the air to inhibit the combustion reaction. At the same time, polybenzimidazole can form a dense carbon layer at high temperature to prevent the transfer of heat and oxygen, thereby improving the flame retardancy of the cable. The mica particles themselves have good insulating properties. The silicon-oxygen tetrahedron and aluminum-oxygen octahedron in their molecular structure form a layered structure by sharing oxygen atoms, which can effectively prevent the passage of current. When the mica particles are coated with polybenzimidazole, the molecular chains of the polybenzimidazole can react with groups such as hydroxyl groups on the surface of the mica particles. The interaction between the two enhances the bonding force between the two and further improves the insulation effect; in addition, through two phosphate solution immersion treatments, a uniform coating may be formed on the surface of the polybenzimidazole-coated mica particles, and the ester group in the phosphate ester molecule may form a hydrogen bond with the nitrogen atom in the polybenzimidazole molecule, or interact weakly with the chlorine atom on the polyvinyl chloride resin molecular chain, thereby further enhancing the flame retardant properties of the polybenzimidazole-coated mica particles and their compatibility with the polyvinyl chloride resin, so that the polybenzimidazole-coated mica particles can be evenly dispersed in the polyvinyl chloride resin to form a physical barrier, thereby preventing the transfer of heat and oxygen, and improving the flame retardant and insulation properties of the cable.
[0028] (2) The solid shell formed by epoxy resin in the repair microcapsule of the present invention is like a protective cover, which tightly wraps the repair agent such as polyurethane prepolymer therein. When subjected to a certain external force or high temperature, the repair agent will be released. The polyurethane prepolymer has good flexibility and can adapt to various deformations such as bending and stretching of the cable during use. When cracks appear in the cable, the polyurethane prepolymer can flow into the cracks and fill them according to the shape of the cracks. It will not crack again due to the deformation of the cable. At the same time, its adhesiveness can cooperate with sodium dodecyl sulfate and the like to make the repair agent and the cable material closely combined to form a strong connection. In addition, the epoxy in the epoxy resin The groups can undergo a ring-opening reaction with the active groups in the cable. Taking the hydroxyl group as an example, the oxygen atom of the epoxy group combines with the hydrogen atom in the hydroxyl group, and at the same time, the carbon atom of the epoxy group forms a new covalent bond with the molecular chain where the hydroxyl group is located. This force can enhance the cable's ability to withstand stress. When the cable is stretched or bent, the covalent bonds in the repaired area can effectively transfer stress and avoid cracking of the damaged area again; the lone pair of electrons on the nitrogen-containing groups in the repair microcapsules can attack the chlorine atoms on the polyvinyl chloride resin molecular chain, causing the chlorine atoms to detach from the molecular chain. At the same time, the nitrogen atoms form new covalent bonds with the carbon atoms, thereby improving the stability of the cable and achieving a relatively long-lasting flame retardant and insulating effect. DETAILED DESCRIPTION
[0029] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0030] Example 1
[0031] A preparation process of a flame-retardant insulated polyvinyl chloride cable, the preparation process of this embodiment comprises the following steps:
[0032] (1) adding polyvinyl chloride resin, polybenzimidazole-coated mica particles, and repair microcapsules into a high-speed mixer and mixing and stirring to obtain material 1;
[0033] (2) adding a plasticizer, a stabilizer and a lubricant to the material 1, stirring and then ultrasonically treating, to obtain a material 2;
[0034] (3) placing the second material in a twin-screw extruder for melt extrusion and then placing it on a roller for refining to obtain a flame-retardant insulating polyvinyl chloride material;
[0035] (4) Extruding the flame-retardant insulating material on the outer surface of the wire core and cooling it to obtain a flame-retardant insulated polyvinyl chloride cable.
[0036] The mass ratio of polyvinyl chloride resin, polybenzimidazole-coated mica particles and repair microcapsules in step (1) of this embodiment is 5.7:2.1:0.9; the molecular weight of the polyvinyl chloride resin is 180,000; the parameters of the high-speed stirrer are: stirring temperature is 100°C, stirring speed is 1200 rpm, and stirring time is 20 min.
[0037] The preparation method of the polybenzimidazole coated mica particles of this embodiment is:
[0038] V1, 0.8 parts by weight of polybenzimidazole and 4 parts by weight of N,N-dimethylacetamide were mixed, and the mixture was stirred at 60° C. and 100 rpm for 1.2 h to obtain a polybenzimidazole solution;
[0039] V2. Immerse mica particles with an average particle size of 50 μm in a phosphate solution, perform ultrasonic treatment for 30 min, filter with a 500-mesh filter cloth, wash with anhydrous ethanol, and then dry in an oven at 80° C. for 3 h to obtain treated mica particles;
[0040] V3, 1.5 parts by weight of the treated mica particles, 6 parts by weight of the polybenzimidazole solution, 0.3 parts by weight of the nonylphenol polyoxyethylene ether solution and 0.1 parts by weight of γ-aminopropyltriethoxysilane were mixed, and stirred at 80° C. and 30 rpm for 2 h to obtain a mixture;
[0041] V4. The mixture was immersed in a phosphate solution, ultrasonicated for 10 minutes, filtered with a 500-mesh filter cloth, and washed with anhydrous ethanol to obtain polybenzimidazole-coated mica particles.
[0042] The phosphate ester solutions in this embodiment are composed of phosphate ester and anhydrous ethanol in a mass ratio of 0.8:9; the nonylphenol polyoxyethylene ether solution in step V3 is composed of nonylphenol polyoxyethylene ether and anhydrous ethanol in a mass ratio of 2.3:0.4.
[0043] The parameters of the ultrasonic step in this embodiment are: the ultrasonic frequency is 50 kHz and the ultrasonic temperature is 40°C.
[0044] The preparation method of the repair microcapsule of this embodiment is:
[0045] W1. Add 1.8 parts by weight of epoxy resin to 6 parts by weight of acetone, then add 0.2 parts by weight of diethylenetriamine, and stir at 50 rpm for 1 hour to obtain a shell material solution;
[0046] W2, adding 0.8 parts by weight of polyurethane prepolymer to 6 parts by weight of deionized water, and then adding 0.016 parts by weight of sodium lauryl sulfate, and stirring at 800 rpm to obtain a repair agent emulsion;
[0047] W3. Mix 1.2 parts by weight of the repair agent emulsion and 2.5 parts by weight of the shell material solution, stir at 45°C at a speed of 1000 rpm for 2 hours, filter with a 200-mesh filter cloth, wash with deionized water, and then dry in an oven at 70°C for 5 hours to obtain repair microcapsules.
[0048] The mass ratio of material 1, plasticizer, stabilizer and lubricant in step (2) of this embodiment is 5:0.7:0.05:0.01, wherein the plasticizer is dioctyl phthalate, the stabilizer is calcium zinc stabilizer, and the lubricant is polyethylene wax; the parameters of the ultrasonic treatment step are: ultrasonic frequency is 50 kHz, ultrasonic temperature is 55°C, and ultrasonic time is 10 min.
[0049] The temperature of the melt extrusion in step (3) of this embodiment is 195°C, and the temperature of the roller mill is 175°C.
[0050] The parameters of the extrusion step in step (4) of this embodiment are: extrusion temperature of 220° C., extrusion speed of 6 m / min, and extrusion pressure of 7 MPa; the parameters of the cooling step are: cooling temperature of 8° C., and cooling time of 6 min.
[0051] Example 2
[0052] A preparation process of a flame-retardant insulated polyvinyl chloride cable, the preparation process of this embodiment comprises the following steps:
[0053] (1) adding polyvinyl chloride resin, polybenzimidazole-coated mica particles, and repair microcapsules into a high-speed mixer and mixing and stirring to obtain material 1;
[0054] (2) adding a plasticizer, a stabilizer and a lubricant to the material 1, stirring and then ultrasonically treating, to obtain a material 2;
[0055] (3) placing the second material in a twin-screw extruder for melt extrusion and then placing it on a roller for refining to obtain a flame-retardant insulating polyvinyl chloride material;
[0056] (4) Extruding the flame-retardant insulating material on the outer surface of the wire core and cooling it to obtain a flame-retardant insulated polyvinyl chloride cable.
[0057] The mass ratio of polyvinyl chloride resin, polybenzimidazole-coated mica particles and repair microcapsules in step (1) of this embodiment is 7.1:2.6:1.3; the molecular weight of the polyvinyl chloride resin is 220,000; the parameters of the high-speed stirrer are: stirring temperature is 140°C, stirring speed is 1800 rpm, and stirring time is 40 min.
[0058] The preparation method of the polybenzimidazole coated mica particles of this embodiment is:
[0059] V1, 1.5 parts by weight of polybenzimidazole and 10 parts by weight of N,N-dimethylacetamide were mixed, and the mixture was stirred at 80° C. and 500 rpm for 1.8 h to obtain a polybenzimidazole solution;
[0060] V2. Immerse mica particles with an average particle size of 70 μm in a phosphate solution, perform ultrasonic treatment for 40 min, filter with a 500-mesh filter cloth, wash with anhydrous ethanol, and then dry in an oven at 80° C. for 3 h to obtain treated mica particles;
[0061] V3, 2.5 parts by weight of the treated mica particles, 8.2 parts by weight of a polybenzimidazole solution, 0.8 parts by weight of a nonylphenol polyoxyethylene ether solution and 0.5 parts by weight of γ-aminopropyltriethoxysilane were mixed, and stirred at 120° C. and 70 rpm for 3 h to obtain a mixture;
[0062] V4. The mixture was immersed in a phosphate solution, ultrasonicated for 20 minutes, filtered with a 500-mesh filter cloth, and washed with anhydrous ethanol to obtain polybenzimidazole-coated mica particles.
[0063] The phosphate ester solutions in this embodiment are composed of phosphate ester and anhydrous ethanol in a mass ratio of 1.1:9.5; the nonylphenol polyoxyethylene ether solution in step V3 is composed of nonylphenol polyoxyethylene ether and anhydrous ethanol in a mass ratio of 3:0.8.
[0064] The parameters of the ultrasonic step in this embodiment are: ultrasonic frequency is 60 kHz, and ultrasonic temperature is 50°C.
[0065] The preparation method of the repair microcapsule of this embodiment is:
[0066] W1. Add 3 parts by weight of epoxy resin to 8 parts by weight of acetone, then add 0.6 parts by weight of diethylenetriamine, and stir at 150 rpm for 2 hours to obtain a shell material solution;
[0067] W2, adding 2 parts by weight of polyurethane prepolymer to 12 parts by weight of deionized water, and then adding 0.04 parts by weight of sodium lauryl sulfate, and stirring at a speed of 2000 rpm to obtain a repair agent emulsion;
[0068] W3. Mix 1.9 parts by weight of the repair agent emulsion and 3.1 parts by weight of the shell material solution, stir at 65°C at a speed of 1500 rpm for 3 hours, filter with a 200-mesh filter cloth, wash with deionized water, and then dry in an oven at 70°C for 5 hours to obtain repair microcapsules.
[0069] The mass ratio of material 1, plasticizer, stabilizer and lubricant in step (2) of this embodiment is 6:1.1:0.12:0.05, wherein the plasticizer is dioctyl phthalate, the stabilizer is calcium zinc stabilizer, and the lubricant is polyethylene wax; the parameters of the ultrasonic treatment step are: ultrasonic frequency is 60 kHz, ultrasonic temperature is 75°C, and ultrasonic time is 20 min.
[0070] The temperature of the melt extrusion in step (3) of this embodiment is 215°C, and the temperature of the roller mill is 195°C.
[0071] The parameters of the extrusion step in step (4) of this embodiment are: extrusion temperature of 260° C., extrusion speed of 10 m / min, and extrusion pressure of 9 MPa; the parameters of the cooling step are: cooling temperature of 8° C., and cooling time of 6 min.
[0072] Example 3
[0073] A preparation process of a flame-retardant insulated polyvinyl chloride cable, the preparation process of this embodiment comprises the following steps:
[0074] (1) adding polyvinyl chloride resin, polybenzimidazole-coated mica particles, and repair microcapsules into a high-speed mixer and mixing and stirring to obtain material 1;
[0075] (2) adding a plasticizer, a stabilizer and a lubricant to the material 1, stirring and then ultrasonically treating, to obtain a material 2;
[0076] (3) placing the second material in a twin-screw extruder for melt extrusion and then placing it on a roller for refining to obtain a flame-retardant insulating polyvinyl chloride material;
[0077] (4) Extruding the flame-retardant insulating material on the outer surface of the wire core and cooling it to obtain a flame-retardant insulated polyvinyl chloride cable.
[0078] The mass ratio of polyvinyl chloride resin, polybenzimidazole-coated mica particles and repair microcapsules in step (1) of this embodiment is 6.4:2.35:1.1; the molecular weight of the polyvinyl chloride resin is 200,000; the parameters of the high-speed stirrer are: stirring temperature is 120°C, stirring speed is 1500 rpm, and stirring time is 30 min.
[0079] The preparation method of the polybenzimidazole coated mica particles of this embodiment is:
[0080] V1, 1.15 parts by weight of polybenzimidazole and 7 parts by weight of N,N-dimethylacetamide were mixed, and the mixture was stirred at 70° C. and 300 rpm for 1.5 h to obtain a polybenzimidazole solution;
[0081] V2. Immerse mica particles with an average particle size of 60 μm in a phosphate solution, perform ultrasonic treatment for 35 min, filter with a 500-mesh filter cloth, wash with anhydrous ethanol, and then dry in an oven at 80° C. for 3 h to obtain treated mica particles;
[0082] V3, 2 parts by weight of the treated mica particles, 7.1 parts by weight of a polybenzimidazole solution, 0.55 parts by weight of a nonylphenol polyoxyethylene ether solution and 0.3 parts by weight of γ-aminopropyltriethoxysilane were mixed, and stirred at 100° C. and 50 rpm for 2.5 h to obtain a mixture;
[0083] V4. The mixture was immersed in a phosphate solution, ultrasonicated for 15 minutes, filtered with a 500-mesh filter cloth, and washed with anhydrous ethanol to obtain polybenzimidazole-coated mica particles.
[0084] The phosphate ester solutions in this embodiment are composed of phosphate ester and anhydrous ethanol in a mass ratio of 0.95:9.25; the nonylphenol polyoxyethylene ether solution in step V3 is composed of nonylphenol polyoxyethylene ether and anhydrous ethanol in a mass ratio of 2.65:0.6.
[0085] The parameters of the ultrasonic step in this embodiment are: the ultrasonic frequency is 55 kHz and the ultrasonic temperature is 45°C.
[0086] The preparation method of the repair microcapsule of this embodiment is:
[0087] W1, add 2.4 parts by weight of epoxy resin to 7 parts by weight of acetone, then add 0.4 parts by weight of diethylenetriamine, and stir at 100 rpm for 1.5 hours to obtain a shell material solution;
[0088] W2, adding 1.4 parts by weight of polyurethane prepolymer to 9 parts by weight of deionized water, and then adding 0.028 parts by weight of sodium lauryl sulfate, and stirring at a speed of 1400 rpm to obtain a repair agent emulsion;
[0089] W3. Mix 1.55 parts by weight of the repair agent emulsion and 2.8 parts by weight of the shell material solution, stir at 55°C at a speed of 1250 rpm for 2.5 hours, filter with a 200-mesh filter cloth, wash with deionized water, and dry in an oven at 70°C for 5 hours to obtain repair microcapsules.
[0090] The mass ratio of material 1, plasticizer, stabilizer and lubricant in step (2) of this embodiment is 5.5:0.9:0.085:0.03, wherein the plasticizer is dioctyl phthalate, the stabilizer is calcium zinc stabilizer, and the lubricant is polyethylene wax; the parameters of the ultrasonic treatment step are: ultrasonic frequency is 55 kHz, ultrasonic temperature is 65°C, and ultrasonic time is 15 min.
[0091] The temperature of the melt extrusion in step (3) of this embodiment is 205°C, and the temperature of the roller mill is 185°C.
[0092] The parameters of the extrusion step in step (4) of this embodiment are: extrusion temperature of 240° C., extrusion speed of 8 m / min, and extrusion pressure of 8 MPa; the parameters of the cooling step are: cooling temperature of 8° C., and cooling time of 6 min.
[0093] Comparative Example 1
[0094] On the basis of Example 3, the phosphate ester solution immersion treatment in step V2 is removed, and other conditions are consistent with Example 3.
[0095] Comparative Example 2
[0096] On the basis of Example 3, the phosphate ester solution immersion treatment in step V4 is removed, and other conditions are consistent with Example 3.
[0097] Comparative Example 3
[0098] On the basis of Example 3, the repair capsule was removed and replaced with an equal weight of polyvinyl chloride resin, and other conditions were consistent with Example 3.
[0099] The flame-retardant insulating polyvinyl chloride materials prepared in Examples 1-3 and Comparative Examples 1-3 were used as samples, and various properties thereof were tested.
[0100] 1. Flame retardant test
[0101] The flame retardant grade of the samples was tested according to GB / T2408-2008. The test results are shown in Table 1 below.
[0102] Table 1
[0103] Flame retardant grade Example 1 V-0 Example 2 V-0 Example 3 V-0 Comparative Example 1 V-1 Comparative Example 2 V-2 Comparative Example 3 V-2
[0104] As can be seen from Table 1, the flame-retardant insulating polyvinyl chloride materials prepared in Examples 1-3 of the present invention have good flame retardant properties, and are superior to Comparative Examples 1-3. The present invention uses two phosphate solution impregnation treatments successively. The first phosphate solution may form a uniform coating on the surface of the polybenzimidazole-coated mica particles, and the ester group in the phosphate ester molecule may form a hydrogen bond with the nitrogen atom in the polybenzimidazole molecule, thereby enhancing the flame retardant properties of the polybenzimidazole-coated mica particles. The second time, the phosphate solution whose binding force may be weakened or lost is repaired, and a more uniform and stable coating is formed on the surface of the polybenzimidazole-coated mica particles, further strengthening the interaction with the polybenzimidazole molecules, enhancing the flame retardant effect, and improving the compatibility of the polybenzimidazole-coated mica particles with the polyvinyl chloride resin. The changes in Comparative Examples 1 and 2 cannot achieve the expected effect, so the flame retardant properties are weakened; Comparative Example 3 removes the repair microcapsules, so that the polyvinyl chloride cable cannot effectively transmit stress at high temperatures and prevent the spread of cracks, so the flame retardant ability is weakened.
[0105] 2. Insulation test
[0106] According to GB / T40719-2021, the volume resistivity of the sample is tested by the three-electrode method to characterize the insulation performance. The test results are shown in Table 2 below.
[0107] Table 2
[0108] Volume resistivity (Ω·cm) Example 1 <![CDATA[9.92×10 16 ]]> Example 2 <![CDATA[1.18×10 17 ]]> Example 3 <![CDATA[1.55×10 17 ]]> Comparative Example 1 <![CDATA[8.85×10 16 ]]> Comparative Example 2 <![CDATA[7.64×10 16 ]]> Comparative Example 3 <![CDATA[1.79×10 17 ]]>
[0109] It can be seen from Table 2 that the volume resistivity of the flame-retardant insulating polyvinyl chloride materials prepared in Examples 1-3 of the present invention is ≥9.92×10 16 , having good insulation performance. The present invention makes the polybenzimidazole-coated mica particles dispersed more evenly in the polyvinyl chloride resin through two impregnation treatments. This uniform distribution forms a more effective physical barrier, reduces the possible local current concentration area, and thus improves the insulation performance of the cable as a whole, so the volume resistivity of Comparative Examples 1 and 2 is weaker than that of Example 3.
[0110] 3. Mechanical properties test
[0111] The mechanical properties of the test samples according to GB / T1040-2006 include tensile strength (MPa) and elongation at break (%). The test results are shown in Table 3 below.
[0112] Table 3
[0113] Tensile strength(MPa) Elongation at break (%) Example 1 21.0 309 Example 2 21.8 313 Example 3 22.5 318 Comparative Example 1 18.9 250 Comparative Example 2 18.2 246 Comparative Example 3 19.3 255
[0114] As shown in Table 3, the flame-retardant insulating polyvinyl chloride materials prepared in Examples 1-3 of the present invention have good tensile strength and elongation at break, and are better than Comparative Examples 1-3. In Comparative Examples 1 and 2, the primary phosphate solution impregnation treatment is removed, so the bonding force between the polybenzimidazole-coated mica particles and the polyvinyl chloride resin is relatively weakened, affecting the mechanical properties of the material in terms of tensile strength and elongation at break; although the polyvinyl chloride resin is added to Comparative Example 3, there is only a small increase in performance, rather than the effect of internal interaction and external mutual influence that can be achieved by the repair microcapsules. When stretched by external force, the internal repair microcapsules of Example 3 release polyurethane prepolymers to penetrate into the gaps to fill and repair, and at the same time enhance the bonding between each other to avoid cracking again or crack expansion. Comparative Example 3 does not have such internal repair when it breaks, so the performance is worse than that of Example 3.
[0115] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A process for preparing a flame-retardant insulated polyvinyl chloride cable, characterized in that: The preparation process comprises the following steps: (1) adding polyvinyl chloride resin, polybenzimidazole-coated mica particles, and repair microcapsules into a high-speed mixer and mixing and stirring to obtain material 1; (2) adding a plasticizer, a stabilizer and a lubricant to the material 1, stirring and then ultrasonically treating to obtain a material 2; (3) placing the second material in a twin-screw extruder for melt extrusion and then placing it on a roller for refining to obtain a flame-retardant insulating polyvinyl chloride material; (4) Extruding the flame-retardant insulating material on the outer surface of the wire core and cooling it to obtain a flame-retardant insulated polyvinyl chloride cable.
2. The process for preparing a flame-retardant insulated polyvinyl chloride cable according to claim 1, characterized in that: In step (1), the mass ratio of the polyvinyl chloride resin, the polybenzimidazole-coated mica particles and the repair microcapsules is 5.7-7.1:2.1-2.6:0.9-1.3; the molecular weight of the polyvinyl chloride resin is 180,000-220,000; the parameters of the high-speed stirrer are: stirring temperature is 100-140° C., stirring speed is 1200-1800 rpm, and stirring time is 20-40 min.
3. The process for preparing a flame-retardant insulated polyvinyl chloride cable according to claim 2, characterized in that: The preparation method of the polybenzimidazole coated mica particles is: V1. Mix 0.8-1.5 parts by weight of polybenzimidazole and 4-10 parts by weight of N,N-dimethylacetamide, and stir at 60-80° C. and 100-500 rpm for 1.2-1.8 hours to obtain a polybenzimidazole solution; V2. Immerse mica particles with an average particle size of 50-70 μm in a phosphate solution, perform ultrasonic treatment for 30-40 min, filter with a 500-mesh filter cloth, wash with anhydrous ethanol, and then dry in an oven at 80° C. for 3 h to obtain treated mica particles; V3, 1.5-2.5 parts by weight of the treated mica particles, 6-8.2 parts by weight of a polybenzimidazole solution, 0.3-0.8 parts by weight of a nonylphenol polyoxyethylene ether solution and 0.1-0.5 parts by weight of γ-aminopropyltriethoxysilane are mixed, and stirred at 80-120° C. and 30-70 rpm for 2-3 hours to obtain a mixture; V4. Immerse the mixture in a phosphate solution, perform ultrasonic treatment for 10-20 minutes, filter with a 500-mesh filter cloth, and wash with anhydrous ethanol to obtain polybenzimidazole-coated mica particles.
4. The process for preparing a flame-retardant insulated polyvinyl chloride cable according to claim 3, characterized in that: The phosphate ester solution is composed of phosphate ester and anhydrous ethanol in a mass ratio of 0.8-1.1:9-9.5; the nonylphenol polyoxyethylene ether solution in step V3 is composed of nonylphenol polyoxyethylene ether and anhydrous ethanol in a mass ratio of 2.3-3:0.4-0.
8.
5. The process for preparing a flame-retardant insulated polyvinyl chloride cable according to claim 3, characterized in that: The parameters of the ultrasonic step are: ultrasonic frequency is 50-60kHz, and ultrasonic temperature is 40-50°C.
6. The process for preparing a flame-retardant insulated polyvinyl chloride cable according to claim 2, characterized in that: The preparation method of the repair microcapsule is as follows: W1. Add 1.8-3 parts by weight of epoxy resin to 6-8 parts by weight of acetone, then add 0.2-0.6 parts by weight of diethylenetriamine, and stir at 50-150 rpm for 1-2 hours to obtain a shell material solution; W2, adding 0.8-2 parts by weight of polyurethane prepolymer to 6-12 parts by weight of deionized water, and then adding 0.016-0.04 parts by weight of sodium lauryl sulfate, and stirring at a speed of 800-2000 rpm to obtain a repair agent emulsion; W3. Mix 1.2-1.9 parts by weight of the repair agent emulsion and 2.5-3.1 parts by weight of the shell material solution, stir at 45-65°C at a speed of 1000-1500 rpm for 2-3 hours, filter with a 200-mesh filter cloth after stirring, wash with deionized water, and dry in an oven at 70°C for 5 hours to obtain repair microcapsules.
7. The process for preparing a flame-retardant insulated polyvinyl chloride cable according to claim 1, characterized in that: In step (2), the mass ratio of material 1, plasticizer, stabilizer and lubricant is 5-6:0.7-1.1:0.05-0.12:0.01-0.05; the parameters of the ultrasonic treatment step are: ultrasonic frequency is 50-60kHz, ultrasonic temperature is 55-75°C, and ultrasonic time is 10-20min.
8. The process for preparing a flame-retardant insulated polyvinyl chloride cable according to claim 1, characterized in that: The temperature of the melt extrusion in step (3) is 195-215°C, and the temperature of the roller milling is 175-195°C.
9. The process for preparing a flame-retardant insulated polyvinyl chloride cable according to claim 1, characterized in that: The parameters of the extrusion step in step (4) are: extrusion temperature of 220-260° C., extrusion speed of 6-10 m / min, and extrusion pressure of 7-9 MPa; the parameters of the cooling step are: cooling temperature of 8° C. and cooling time of 6 min.
